Through deaf eyes : a photographic history of an American community - Baynton, Douglas C.; Gannon, Jack R.; Bergey, Jean Lindquist (Washington, D.C. : Gallaudet University Press, 2007)
In 2001, the Smithsonian Institution presented the landmark photographic exhibition History Through Deaf Eyes, representing nearly 200 years of United States deaf history. Drawing heavily on the extensive archives at Gallaudet University, the curators created an exhibition that drew more than 400,000 people viewed at the Smithsonian and in 12 cities during a five-year national tour. Its popularity prompted the production of a documentary film for national broadcast on the Public Broadcasting System. Now, the photographs, quotes, and stories from this remarkable exhibit and documentary have been assembled in a book of stunning beauty and poignant images, Through Deaf Eyes: A Photographic History of an American Community. Featuring more than 200 full-color photographs, Through Deaf Eyes depicts the story of Deaf America and also affords readers the opportunity to learn about the nation's broader history. The values and judgments of society have had an impact on the education, employment, and family life of deaf people, while historical eras often can be illuminated by examination through a Deaf lens. Photographs reveal the character of Deaf people in school settings, the workplace, during wartime, and using their cultural signature, American Sign Language. For both deaf and hearing readers, the Deaf community portrayed in Through Deaf Eyes offers a unique and fascinating perspective on the value of human difference. ... Publisher description.
Chapter 2 The Advent of Deaf Education in the United States 10 -- Chapter 3 The Formation of a Deaf Community 28 -- Chapter 4 The Struggle over Sign Language 60 -- Chapter 5 In Time of War and Economic Depression 84 -- Chapter 6 Access and Awareness 112.
Includes bibliographical references (p. [147]) and index.
Keywords: Deaf people -- United States -- History; Deaf people -- United States -- History -- Pictorial works; Deaf; United States; History; Pictorial works